ANALISIS DESKRIPTIF FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN ULANG PELAYANAN PASIEN RAWAT INAP PESERTA BPJS DI PUSKESMAS GEMPOL - Izza Afkarina Mutiara; Titis Eka Gusti; Eka Yusmanisari (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
Utilization of health services in Indonesia from 7,300 respondents who experienced hospitalization was 53.36% in urban areas and 46.64% in rural areas in the last 1 year. Most of the patients who experienced hospitalization were treated at government hospitals 49.7%, followed by private hospitals at 28.6% and the rest were treated elsewhere. The utilization of inpatient services at Gempol Health Center is still low because the indicator values for inpatient services are not up to standard. The purpose of this study was to analyze the factors related to interest in utilization and interest in re-utilizing services for inpatients BPJS participants at Gempol Health Center. This research is descriptive quantitative with a cross-sectional approach. The sample of this research is 30 BPJS inpatients. Data collection techniques are interviews and questionnaires with univariate analysis. Frequency of respondents based on gender characteristics: 12 men (40%), 18 women (60%), by age category: 7 teenagers (23.3%), 20 adults (66.7%), and 3 elderly people (10%), based on their latest education: 5 people with low education (16,7%), 25 people with higher education (83,3%). The Frequency with which they are interested in service reuse: 18 people are interested (60 %) were not interested as many as 12 people.